Assessing parents’ satisfaction with their parental role for a more effective partnerships between families and schools - Martinez-Gonzalez, Raquel-Amaya; Rodríguez-Ruiz, Beatriz (International Journal about Parents in Education, 2023)
This study is framed within the field of family education family-school-community partnerships considering ways by which schools might help parents to be better involved in their children’s education; one of this ways is performing parenting programmes within the school in areas of interest for parents. The objective is to identify parents’ educational needs regarding their role with small children to help them to answer those needs by means of a parenting programme. Accordingly, the study has been organized in two phases: the first one is devoted to assess and identify parental needs and the second one to describe and evaluate a parenting programme. Both qualitative and quantitative procedures to gather information have been used: parents’ questionnaires, group dynamics with parents and semi-structured interviews. The sample is composed of 54 Spanish rural and urban parents with small children. Results in the assessment phase indicate that although most parents are satisfied with their parental role, many have doubts about how to solve problems and help their children to control their behaviour better. The positive results of the parenting programme in the second phase point out the convenience to design, perform and evaluate educational strategies for empowering parents while upbringing their children.